Assistance for waste data management applications and Smart Drop Box as waste bank digitization tools - Putra Fajar Alam; Widyatasya Agustika; Dino Caesaron (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Based on data from the National Waste Management Information System (SIPSN) that in the 2018-2019 period the population in the Ciamis district was 1,401,423 people, resulting in a fairly large amount of waste generation, around 78,173 tons/day. The amount of waste transported to landfills (TPA) is only 3,327 tons/day. This shows that only 4% of waste has been managed properly in Ciamis Regency, while the remaining 96% has not been handled properly. Therefore, the team of community service (PkM) Telkom University together with Ciamis Regency work together to increase the capacity and capability of the Waste Bank in managing waste digitally through the application of information technology and the Internet of Things. From the results of the usability survey, a score of 64.12 was obtained, which indicates that in the use of the application, better development is still needed, because most people still need assistance in using the application and still need to get used to using the application. This can be anticipated by providing more intense assistance, both directly/offline and online, such as socialization using an online meeting platform. However, feedback on PkM activities given to the community received a percentage of 97.64%, which stated that this activity was accepted by the community and hoped that this program in the future would be in accordance with the needs of the community.